Pembentukan Bank Tanah: Merencanakan Ketersediaan Tanah untuk Percepatan Pembangunan di Indonesia - Maulana Rafi Danendra; Dian Aries Mujiburohman (Widya Bhumi, 2022)
The availability of land is the main instrument for national development in Indonesia. However, the massive development activities undertaken by the government and the public often lead to friction over land management, development, security, and control issues. The presence of a land bank agency is expected to be able to guarantee the availability of land under development for public, social, and economic equity. This research aims to analyze the urgency of establishing a land bank agency, the mechanism of land acquisition as a support for national development, its opportunities, and challenges. A qualitative method with descriptive analysis is applied in this research. The primary and secondary data that have been obtained are analyzed descriptively through data reduction, data presentation, and drawing conclusions related to the existence of land bank entities in Indonesia. Take a look at the results of this research, it indicates that the land bank agency is an agency that is capable to answer problems related to land acquisition for development in Indonesia. The implementation mechanism starts from the process of procurement, management, utilization, and distribution of land. The availability of land by the land bank is not only capable to facilitate the investment climate, but also to avoid the swelling of financing in land acquisition, abandonment of land and land disputes. However, this study suggests that a more specific study is needed regarding the process of transferring land rights and coordination between relevant stakeholders in order to fulfill the object. Ketersediaan tanah menjadi instrumen utama untuk pembangunan nasional di Indonesia. Namun, masifnya kegiatan pembangunan oleh pemerintah dan masyarakat sering kali menimbulkan gesekan permasalahan pengelolaan, pengembangan, pengamanan dan pengendalian atas tanah. Hadirnya badan bank tanah diharapkan mampu menjembatani ketersediaan tanah dalam pembangunan untuk kepentingan umum, sosial dan pemerataan ekonomi. Penelitian ini bertujuan untuk menganalisis urgensi pembentukan badan bank tanah, mekanisme perolehan tanah sebagai penunjang pembangunan nasional, peluang dan tantangannya. Penelitian ini menggunakan metode kualitatif dengan analisis deskriptif. Data primer dan sekunder yang telah diperoleh kemudian dianalisis secara deskriptif melalui reduksi data, penyajian data hingga penarikan kesimpulan terkait dengan keberadaan badan bank tanah di Indonesia. Hasil penelitian menunjukkan bahwa badan bank tanah merupakan badan yang mampu menjawab persoalan terkait dengan pengadaan tanah untuk pembangunan di Indonesia. Mekanisme pelaksanaannya dimulai dari proses pengadaan, pengelolaan, pemanfaatan hingga pendistribusian tanah. Ketersediaan tanah oleh badan bank tanah selain mampu memudahkan iklim investasi, juga mampu menghindarkan pembengkakan pembiayaan dalam pembebasan tanah, penelantaran tanah serta sengketa tanah. Namun demikian, penelitian ini menyarankan perlu dilakukan kajian yang lebih spesifik terkait proses peralihan hak atas tanah dan koordinasi antar stakeholder terkait dalam rangka pemenuhan objeknya.